Hydrogen Sulfide Improves Endothelial Dysfunction via Downregulating BMP4/COX-2 Pathway in Rats with Hypertension. (23rd August 2016) - Xiao, Lin; Dong, Jing-Hui; Jin, Sheng; Xue, Hong-Mei; Guo, Qi; Teng, Xu; Wu, Yu-Ming
Abstract : Aims . We object to elucidate that protective effect of H2 S on endothelium is mediated by downregulating BMP4 (bone morphogenetic protein 4)/cyclooxygenase- (COX-) 2 pathway in rats with hypertension. Methods and Results . The hypertensive rat model induced by two-kidney one-clip (2K1C) model was used. Exogenous NaHS administration (56 μ mol/kg/day, intraperitoneally once a day) reduced mean arterial pressure (MAP) of 2K1C rats from199.9 ± 3.312 mmHg to159.4 ± 5.434 mmHg, while NaHS did not affect the blood pressure in the Sham rats and ameliorated endothelium-dependent contractions (EDCs) of renal artery in 2K1C rats. 2K1C reduced CSE level twofold, decreased plasma levels of H2 S about 6-fold, increased BMP4, Nox2, and Nox4 levels 2-fold and increased markers of oxidative stress MDA and nitrotyrosine 1.5-fold, upregulated the expression of phosphorylation-p38 MAPK 2-fold, and increased protein levels of COX-2 1.5-fold, which were abolished by NaHS treatment. Conclusions . Our results demonstrate that H2 S prevents activation of BMP4/COX-2 pathway in hypertension, which may be involved in the ameliorative effect of H2 S on endothelial impairment. These results throw light on endothelial protective effect of H2 S and provide new target for prevention and therapy of hypertension.